Creating Media with Prescribed Permeability Using the Asymptotic Solution to EM Wave Scattering Problem - Ramm, Alexander G.; Andriychuk, Mykhaylo (IEEE Xplore Digital Library, 2014)
Asymptotic solution to scattering problem of electromagnetic (EM) waves by many small impedance particles, embedded in a homogeneous medium, is applied for creating media with prescribed permeability. Physical properties of the particles are described by their boundary impedances. The limiting equation is obtained for the effective EM field in the resulting medium. The proposed theory allows one to create a medium with a desirable spatially inhomogeneous permeability. The main new physical result is the explicit analytic formula for the permeability μ(x) of the limiting medium. The computational results confirm a possibility to create the media with various distributions of μ(x).
Keywords: EM Wave Scattering, Desired Permeability, Modeling Results